PENGARUH SOSIAL MEDIA MARKETING, ELEKTRONIK WORD OF MOUTH DAN PERSEPSI HARGA TERHADAP NIAT BELI PADA SMARTPHONE VIVO - Raya, Febby; Saputro, Edy Purwo (MANAJEMEN DEWANTARA, 2024)
The aim of this research is to learn how someone can promote a product to attract customers' attention. With social media marketing, customers are interested in buying the products offered. Apart from that, promoting products through social media marketing is also offered using the electronic word of mouth method, namely through media delivered directly by word of mouth. Before offering to customers, determining the price is also important because price also influences customers' purchasing intentions. The research method used is a quantitative approach in this research used with various methods. The criteria taken to fulfill the research were people who had never purchased a Vivo smartphone product with samples obtained from more than 100 respondents. This research also comes from a survey obtained from a questionnaire using a 5 point Likert scale. The survey has been distributed to respondents in order to inform the audience to know the product being researched in order to determine the significant results and profits obtained from social media marketing and the influence of price so that they make a purchase of the product. The results obtained from this research show that the analytical method produces an insignificant influence between price perception and purchase intention. So the results of this research show that social media marketing and electronic word of mouth influence purchase intentions significantly. Meanwhile, price perception does not influence customers' purchase intentions when buying a Vivo smartphone.